Management of Gastric Varices Unsuccessfully Treated by Balloon-Occluded Retrograde Transvenous Obliteration: Long-Term Follow-Up and Outcomes. (21st December 2013) - Uchiyama, Fumio; Murata, Satoru; Onozawa, Shiro; Nakazawa, Ken; Sugihara, Fumie; Yasui, Daisuke; Narahara, Yoshiyuki; Uchida, Eiji; Amano, Yasuo; Kumita, Shin-ichiro
Abstract : Our aim was to evaluate the long-term efficacy and safety of percutaneous transhepatic obliteration (PTO) alone and combined with balloon-occluded retrograde transvenous obliteration (BRTO) for gastroesophageal varices refractory to BRTO alone. Between July 1999 and December 2010, 13 patients with gastroesophageal varices refractory to BRTO were treated with PTO ( n = 6) or a combination of PTO and BRTO ( n = 7). We retrospectively investigated the rates of survival, recurrence, or worsening of the varices; hepatic function before and after the procedure; and complications. The procedure achieved complete obliteration or significant reduction of the varices in all 13 patients without major complications. During follow-up, the varices had recurred in 2 patients, of which one had hepatocellular carcinoma, and the other died suddenly from variceal rebleeding 7 years after PTO. The remaining 11 patients did not experience worsening of the varices and showed significant improvements in the serum ammonia levels and prothrombin time. The mean follow-up period was 90 months, and the cumulative survival rate at 1, 3, and 5 years was 92.9%, 85.7%, and 85.7%, respectively. Both PTO and combined PTO and BRTO seem as safe and effective procedures for the treatment of gastroesophageal varices refractory to BRTO alone.